Single-Center Evaluation of Treatment Success Using Two Different Protocols for MRI–Guided Transurethral Ultrasound Ablation of Localized Prostate Cancer - Hatiboglu, Gencay; Popeneciu, Valentin; Bonekamp, David; Burtnyk, Mathieu; Staruch, Robert; Distler, Florian; Radtke, Jan Philipp; Motsch, Johann; Schlemmer, Heinz Peter; Pahernik, Sascha; Nyarangi-Dix, Joanne (Frontiers in Oncology, 2021)
OBJECTIVES: To assess differences in 24-month oncologic and functional outcomes in men with low to intermediate-risk prostate cancer treated with MRI-guided transurethral ultrasound ablation (TULSA) using intentionally conservative versus intensified treatment parameters. PATIENTS AND METHODS: Patients from a single center involved in two multicenter trials were included in this analysis. This included 14 of 30 patients with Gleason 3+3 from a Phase I study using intentionally conservative treatment parameters, and 15 of 115 patients with Gleason ≤ 3+4 from a pivotal study using intensified parameters. Follow-up data compared across these cohorts included 12-month biopsy and MRI for all patients, and 24-month PSA, micturition and quality of life (IIEF, IPSS, IPSS-QOL). The prognostic value of baseline parameters and PSA kinetics on 12-month histological recurrence was evaluated by logistic regression. RESULTS: 12-month biopsy revealed clinically significant residual disease in 4 (29%) and 2 (14%) patients from the Phase I and pivotal studies , respectively. PSA nadir was 0.7 ng/ml for Phase I and 0.5 ng/ml for pivotal study patients. Patient age at diagnosis, use of MRI fusion/systematic prostate biopsy, number of obtained cores at initial biopsy, PSA course, and PSA nadir were identified as prognostic factors for treatment success. All but one patient from each cohort maintained erection firmness sufficient for penetration. No cases of pad use were reported at 24 months. There were no Grade 4 or higher adverse events, and no late toxicity related to the procedure. CONCLUSION: Two-year follow-up demonstrated the efficacy of TULSA for the treatment of localized prostate cancer, and the durability of PSA and functional outcomes. Intensifying treatment parameters in the pivotal trial had no impact on safety or functional outcomes through 24 months, while reducing the recurrence rate for clinically significant disease. Careful patient selection by MRI fusion/systematic prostate biopsy and adequate follow-up through routine 12-month biopsy are recommended.